(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
In modern society, there is a complete restructuring of the institution of disability. It is important to study the opinion of actors of the educational environment. This article aims to analyze the peculiarities of teachers’ perceptions and readiness for inclusive education. As a research method, the questionnaire method was used, which effectively identifies the peculiarities of the attitude of the agents of the educational environment to inclusive education. The authors of the article describe the peculiarity of the current stage of development of the practices of using inclusive education as a social phenomenon. For the first time, teachers’ ideas about bodily atypicality were studied, and the educational environment’s features in the inclusive education system were considered. The dependence of the age of the interviewed teachers on the willingness to develop new educational programs within inclusions is established. It was revealed that the older the teacher, the greater the probability of the classical method of teaching the material and the unavailability to work in inclusive classes. The interviewed teachers propose improving the current situation by attracting additional funding and raising public awareness about inclusive education.